An Evaluation of Substance Abuse Treatment and HIV Education on Safe Sex Practices in Cocaine Dependent Individuals. (4th March 2014) - Winhusen, Theresa M.; Somoza, Eugene C.; Lewis, Daniel F.; Kropp, Frankie; Theobald, Jeff; Elkashef, Ahmed
Abstract : Background. There is a strong association between crack/cocaine use and increased sexual risk behavior, but little research on the efficacy of HIV education for decreasing such behavior in crack/cocaine-addicted individuals in substance abuse treatment. Method. Datasets from two cocaine dependence trials including either one or three HIV education sessions, respectively, were analyzed for changes over time in the proportion of participants practicing safe sex. A pooled dataset from two earlier trials not offering HIV education was also analyzed. Results. We included 83 participants from the 1-session trial and 65 participants from the 3-session trial. Both sets of participants evidenced a significant increase in the proportion of participants having safe sex with casual partners. Participants in the 3-session HIV education study also evidenced a significant increase in the proportion of participants having safe sex with regular partners. In the trials without HIV education, no change in safe sex practices was found, and change in condom use was observed only among female participants. Conclusions. These findings are consistent with recommendations that HIV education/counseling should be provided to individuals in substance abuse treatment. A randomized controlled trial to confirm these results may be warranted. This trial is registered withNCT00033033, NCT00086255, NCT00015106, andNCT00015132 .